Addendum to “Search and Breast Cancer: On Episodic Shifts of Attention over Life Histories of an Illness” - Paul, Michael J.; White, Ryen W.; Horvitz, Eric (1999)
This is a publication addendum for the article "Search and Breast Cancer: On Episodic Shifts of Attention over Life Histories of an Illness", accepted for ACM Transactions on the Web. Ontology.txt contains the Breast Cancer Search Term Ontology referenced in the article. See the README.txt for more details on the file format.
ACM Transactions on the Web